Morphological causatives in Moroccan Arabic: An Optimality-Theoretic account - Loutfi, Ayoub (Lingua Posnaniensis, 2024)
This study investigates the formation of the morphological causative in Moroccan Arabic within the framework of Optimality Theory. The pivotal process involved in this construction is morphological gemination, where the second consonant of the root is doubled (e.g., ktəb kəttəb). A perplexing aspect of this process is its consistent targeting of the second consonant, while excluding ill-formed words such as *kktəb and *ktəbb. In this study, we argue that the linearization of the causative morpheme in MA is governed by phonological well-formedness interacting with the morphological process of causativization, resulting in infixation. This phenomenon exemplifies the Emergence of the Unmarked (McCarthy & Prince 1994; Alderete et al. 1999), where the otherwise inactive markedness constraint *COMPLEXONSET in the language assumes explanatory prominence. The strength of the analysis proposed here lies in treating the infixal process as an outcome of simple and universal constraints, primarily motivated by demands on prosodic well-formedness, without recourse to language-specific templatic patterns. This approach highlights the implications of phonological constraints in capturing morphological processes and suggests that templatic patterns may emerge from phonological well-formedness rather than being innate to the language.